Implementation of an Energy Management System in Colombian Manufacturing - A Methodological Approach (2021)
This paper aims to analyze mechanisms such as the Energy management systems approach in industry 4.0. The paper is a review of techniques for optimizing energy consumption with energy efficiency, advanced metering infrastructure andrational and efficient use of energy to reduce the pollution as well as to strengthen Industry 4.0 models and the monitoring and management opportunities that exist with the implementation of this models in Colombia.